Echinacoside Inhibits Osteoclast Function by Down-Regulating PI3K/Akt/C-Fos to Alleviate Osteolysis Caused by Periprosthetic Joint Infection - Jiang, Tao; Gu, Hanwen; Wei, Jian (Frontiers in Pharmacology, 2022)
Infected osteolysis as a common secondary osteoporosis is associated with excessive osteoclastogenesis and bone resorption. The inhibition of osteoclastogenesis and bone resorption have been demonstrated an effective approach in the treatment of osteolytic diseases. Echinacoside (ECH) is a natural phenylethanoid glycoside with multiple biological functions, including anti-inflammatory, antioxidant, and osteoblast differentiation promotion. However, the effects of ECH on osteoclast differentiation and bone resorption function remain unknown. In vitro, we investigated the effects of ECH on osteoclast differentiation and bone resorption induced by RANKL and its potential mechanisms. In vivo, we established a periprosthetic joint infection (PJI) rat model and demonstrated the changes of infected osteolysis and osteoclasts activities in surgical sites. ECH (20 mg/kg) was injected intraperitoneally after debridement for 4 weeks. Radiological evaluation and bone histomorphometric analysis was performed to assess the efficacy of ECH. The results showed that ECH inhibited osteoclast differentiation, F-actin belts formation, bone resorption function and osteoclast-specific gene expression by preventing NFATc1 translocation, down-regulating its expression and affecting the PI3K/Akt/c-Fos pathway in vitro. ECH also alleviated in vivo PJI-induced osteolysis and maintained bone mass by inhibiting osteoclast activity. Our study indicated that ECH attenuated RANKL-induced osteoclastogenesis and PJI-induced bone loss and was shown as a potentially effective therapeutic agent for osteoclast-related bone diseases.